Subgrade improvement using lime powder, sand and rice husk ash - Mohammed AL-HADHEQ, Abdulghani (Universiti Teknologi PETRONAS, 2017)
Poor subgrade is a common issue In Malaysia that causes the engineers to design thicker highways which considered more costly. However there is different method to improve the subgrade physical methods and chemical methods .in this study add 8% of chemical admixture lime powder, rice husk, and sand is added to stabilize the subgrade .test such as CBR, Proctor compaction test is conducted to determine the strength characteristics and other characteristics tests such as moisture content, plastic, and liquid limit tests. All samples prepared were added with the amount of water at optimum moisture content for CBR testing .for adding the same percentage which is 8% for all samples .all the samples have show incensement for the lime and rice husk ash it was 13.55% and 10.45% respectively as for sand I was 3.1% only.